A concept of crowdfunding in Islam : a critical view / Mazni Natasha Mohd Nasir - Mohd Nasir, Mazni Natasha (Academy of Contemporary Islamic Studies (ACIS), 2017)
Crowdfunding is an innovative process for funding diverse and multiple new ventures, allowing entrepreneurially skilled individuals to request funding from the public or crowd, which in return will get the product. Meanwhile, as a problem is the awareness and understanding of public about this crowdfunding is still lack as well it has been debated for its legality from Sharia’ compliance. Next, the question arises about the elements that follow the conventional practice. Due to lack understand about significant of crowdfunding practice in the socioeconomic. The primary objective was to determine the crowdfunding concept in Islam and to analyze the socio-economic development of crowdfunding in society. In this study a number of crowdfunding as a model to a number of case studies. It uses methods related to the deductive and inductive. Deductive to compare the practice of crowdfunding. Meanwhile, the inductive to give some of the additional strength to the research. At the end of this research, this is the best practice to everyone to generate economic Malaysia. In conclusion, it will hope this research will give benefit to society in Malaysia for the betterment of socioeconomic and education.